Manajemen Wahana Olahraga Rekreasi Susur Goa (Caving) di Goa Pancur Jimbaran Kecamatan Kayen Kabupaten Pati Tahun 2019 (Indonesian Journal for Physical Education and Sport, 2022)
The purpose of this study is to examine the management process to improve the ability of the manager who is less than optimal in serving visitors and has an impact on sports vehicles that have minimal promotion. The research method used in this research is qualitative research with data triangulation method (interviews, observation and documentation). The results of qualitative research emphasize meaning rather than generalizations. The analysis in this study uses inductive data reduction. From the results of the description analysis, it shows that the planning process is classified as good in terms of full tourism infrastructure improvements. The cave tour planning process adheres to the principle of a Comprehensive Approach where all aspects of tourism development including institutional elements and the environment as well as socio-economic implications, as a holistic approach. The organization of the tour management has been included in the tourism awareness group program with directions from the Pati Regency Regent in the Group Discussion Forum. The mobilization function carried out in the management of the cave tourism management is focused on the function of the chairman as the managerial head of its members in carrying out work programs, encouraging members to work sincerely and guiding members to realize work program targets. The implementation of supervision or controlling is carried out incidentally, the chairman evaluates every aspect of the activity and there is no special technique from the chairman to provide supervision to members. The conclusion that can be drawn is that the process of planning, organizing, actuating and controlling functions is going well with various regeneration activities, maintenance and organized tourism promotion processes